Analisis Kualitas Air Sungai Batang Merangin Provinsi Jambi - Vivi Sisca; Leni Marlina (BIOCOLONY, 2019)
The water quality of Sungai Batang Merangin can be monitored through physical, chemical and biological parameters. Water quality research was conducted with temperature research parameters, TSS, PH, DO, COD, metal (Pb, Cd and Hg) and plankton. Water samples were taken in July and August 2017. The result of measurement of water quality parameter of Batang Merangin river was obtained by temperature data of 26-29,5 ° C, maximum TSS 474 mg / L, maximum pH 7, DO maximum of 7.6 mg / L, maximum COD 61.2 mg / l, cadmium metal (Cd) maximum 0.031 mg / l, metal timbale (Pb) averaging <0.02 mg / l, mercury (Hg) averaged <0.001 mg / l, plankton abundance ranged from 31.2-123.2 ind / L, plankton diversity ranged from 0.204-0.672, plankton uniformity between 0.294-0.423, plankton dominance ranged between 0,226-0,706. All physical, chemical and biological parameters are still below the maximum level except for Cadmium metal value at one point according to PP 82 of 2001 and the index value of Diversity is categorized as heavily polluted according to Shannon-Wieners index.